Exploring the aerosol activation properties in coastal shallow convection using cloud- and particle-resolving models - G. Yu; Y. Wang; Z. Wang; X. Shi; X. Shi (Atmospheric Chemistry and Physics)
Aerosols significantly impact the global climate by affecting the Earth's radiative balance and cloud formation. However, conducting cloud-altitude aerosol observations is currently costly and challenging, leading to gaps in accurately assessing aerosol activation properties during cloud formation. In this study, Cloud Model 1 (CM1) is employed to investigate the movement of air parcels under shallow-convection conditions in a coastal area. Subsequently, the evolution of various aerosol populations in the ideal scenarios is simulated by the Particle Monte Carlo (PartMC)–Model for Simulating Aerosol Interactions and Chemistry (MOSAIC) model to investigate their activation properties. It is found that leaving the boundary layer and entering the free atmosphere causes environmental changes in the parcels, which in turn alter the aerosol evolution and the cloud-forming potential. The impact of ascent timing is notably manifested in the concentration of ammonium nitrate rather than other chemical constituents. The rapid formation of ammonium nitrate accelerates the aerosol aging process, thereby modifying the hygroscopicity of the population. The differences between the aerosol populations in the boundary layer and at cloud altitudes highlight the necessity of vertical observations and numerical modeling. In addition, as supersaturation rises from 0.1 % to 1 %, the discrepancy in the cloud condensation nuclei (CCN) activation ratio between the particle-resolved results and the internal mixing assumption increases from 7 % to 30 %. This emphasizes the potential of appropriate mixing-state parameterization in assessing aerosol activation properties. This study advances the understanding of aerosol hygroscopic changes under real weather conditions and offers insights into future modeling of aerosol–cloud microphysics.